Time reference in aphasia: are there differences between tenses and aphasia fluency type? A systematic review and individual participant data meta-analysis - Cordonier, Natacha; Schaffner, Evodie; Zeroual, Lana; Fossard, Marion (Frontiers in Psychology, 2024)
Time reference is used to build the temporal framework of discourse and is essential in ensuring efficient communication. Several studies have reported time reference deficits in fluent and non-fluent aphasia and have shown that tenses (past, present, future) are not all impaired to the same extent. However, there is little consensus on the dissociations between tenses, and the question of the influence of the type of aphasia (fluent vs. non-fluent) on time reference remains open. Therefore, a systematic review and an individual participant data meta-analysis (or mega-analysis) were conducted to determine 1) whether one tense is more impaired than another in fluent and non-fluent aphasia and, if so, 2) which task and speakerrelated factors moderate tense effects. The systematic review resulted in 35 studies reporting the performance in time reference of 392 participants. The mega-analysis was then performed on 23 studies for a total of 232 participants and showed an alteration of past tense compared to present and future tenses in both types of aphasia. The analysis also showed a task and an age effect on time reference but no gender effect, independently of tenses. These results add to our knowledge of time reference in aphasia and have implications for future therapies.